Clinicopathological features and prognosis of coexistence of gastric gastrointestinal stromal tumor and gastric cancer. Issue 45 (November 2016) - Liu, Zhen; Liu, Shushang; Zheng, Gaozan; Yang, Jianjun; Hong, Liu; Sun, Li; Fan, Daiming; Zhang, Hongwei; Feng, Fan
Abstract : Abstract: The coexistence of gastric gastrointestinal stromal tumor (GIST) and gastric cancer is relatively high, and its prognosis is controversial due to the complex and variant kinds of presentation. Thus, the present study aimed to explore the clinicopathological features and prognostic factors of gastric GIST with synchronous gastric cancer. From May 2010 to November 2015, a total of 241 gastric GIST patients were retrospectively enrolled in the present study. The patients with coexistence of gastric GIST and gastric cancer were recorded. The clinicopathological features and prognoses of patients were analyzed. Among 241 patients, 24 patients had synchronous gastric cancer (synchronous group) and 217 patients did not (no-synchronous group). The synchronous group presented a higher percentage of elders (66.7% vs 39.6%, P  = 0.001) and males (87.5% vs 48.4%, P  < 0.001) than the no-synchronous group. The tumor diameter, mitotic index, and National Institutes of Health degree were also significantly different between the 2 groups (all P  < 0.05). The 5-year disease-free survival and disease-specific survival rates of synchronous group were significantly lower than those of no-synchronous group (54.9% vs 93.5%, P  < 0.001; 37.9% vs 89.9%, P  < 0.001, respectively). However, the 5-year overall survival rates between synchronous and gastric cancer groups were comparable (37.9% vs 57.6%, P  = 0.474). The coexistence of gastric GIST and gastric cancer was common in elder male patients. The synchronous GIST was common in low-risk category. The prognosis of gastric GIST with synchronous gastric cancer was worse than that of primary-single gastric GIST, but was comparable with primary-single gastric cancer.